Interferência de fatores bióticos e abióticos na propagação e conservação de Casearia sylvestris Swartz (Salicaceae) - Imatomi, Maristela (2007)
C. sylvestris presents great economic and social importance, being used as phytotherapic. The objective of first chapter was to supply informations on the reproductive phenophase, morphology and seed germination of C. sylvestris, and verify the existence of variability of the germinative behavior according to seed origin. Seeds from two places: Itirapina-SP and Londrina-PR, with 14,5% and 22,86% of moisture contente, respectively, had been germinated, in the absence of light at constant temperatures of 27, 30 and 33 ºC and under fotoperíodo of 12 h and alternating temperature of 20-30 ºC. The effect of growth regulators was verified with solutions of gibberellic acid (10 and 20 mgL-1) or kinetin (5 and 10 mgL-1). The tetrazólium test showed that 32% of the seeds from SP and 66% from PR were viable. Both lots presented the three-phase standard embibition curve, with differences at emission times of the primary root. In the temperature test the excellent band of germination between 27 and 30 ºC was determined for both lots. The use of growth regulators was not efficient to improving the seed performance. Seedlings emerged from SP had been more vigorous (highest values of mass), however shorter than PR lot. After the storage, SP lot presented reduction in the viability and vigor, but PR lot only vigor was reduced. In the second chapter the this objective of the study was to analyze the population structure and the space distribution of C. sylvestris in an area of Cerrado sensu stricto, to promote the reproduction of this species through vegetative propagation, determine the origin of buds in root cuttings through anatomical studies and to inquire the allelopathic interference from in the roots extracts of this species. The space distribution was random e, after the fire occurrence in the area, changed to aggregate. The XII popualation of clones is growth while plant-mother population was not. In the stem cuttings was observed small persentage when mixture of ANA and AIB in higher concentrations. Was used by the other side, root cuttings presented 70% of production shoots. Through the anatomical comments it was proven that it is a root buds and that probably the buds present endogenous and reparative origin. The extract from roots reduced the speed of germination of lettuce and sesame, but it did not modify the germination percentage.